TANTANGAN KEAMANAN DATA DALAM IMPLEMENTASI TEKNOLOGI AI DI AKUNTANSI - Hayati, Dian Indah; Syawitri, Afriosa; Julyazti, Nadya Fritanita; Sulaiman, Ahmad Rahbani (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
Artificial Intelligence (AI) has made a huge impact in transforming the accounting industry by automating various processes, improving operational efficiency, and providing more accurate data analysis for decision-making. However, despite its significant benefits, the application of AI in accounting also brings great challenges, especially in terms of data security. The threat of cyberattacks can undermine the integrity of financial statements and the audit process. In addition, vulnerabilities in AI algorithms used in accounting can enable manipulations that affect analysis results and business decisions. This research aims to identify these key challenges and propose relevant mitigation solutions. Among the solutions discussed are the implementation of blockchain to improve data transparency and security, regular audits to monitor the integrity of AI systems, and employee training to raise awareness of potential cyber threats. With a descriptive approach and literature analysis, this study provides practical guidance for companies to securely integrate AI in their accounting practices.Keywords: Artificial Intelligence (AI), Data Security, Blockchain